The Successful and Novel Treatment of Non-Neurogenic Detrusor-External Sphincter Dyssynergia (DESD) with Botulinum Toxin A. (June 2013) - Kuo, Tricia LC; Ng, Lay Guat
Introduction: Our study aims to examine the treatment outcomes of patients with non-neurogenic detrusor-external sphincter dyssynergia (DESD) after the injection of botulinum toxin A (BTX-A, Botox®) to the external sphincter. Methods: A retrospective review of nine patients with DESD was performed. All patients were diagnosed with the aid of video urodynamic studies. Pre-operative evaluation was standardised using bladder diary, urine microscopy and culture, bedside ultrasound of the kidneys and bladder, and renal function test. Each received BTX-A injection of 50–100U to the external sphincter. The pre-operative and post-operative maximum flow rate (Qmax) and post-void residual urine (PVRU) were objectively compared using paired-samples t test. Results: All the injections were performed from December 2006 to March 2008. Of the nine patients, seven (77.8%) were female and two (22.2%) were male. The mean age was 49.2 years (range 20–64 years). The mean pre-operative maximum flow rate (Qmax) was 9.7±6.26 ml/s. A month later, the post-operative Qmax improved to 16.5±11.3 ml/s. Mean difference in Qmax was 6.76±8.1 ml/s ( P = 0.037). The mean preoperative post void residual urine (PVRU) was 179.2±86.8 ml. This improved to 45.7±44.4 ml post-operatively. The mean difference in PVRU of 133.6±77.2 ml ( P = 0.001). Conclusion: In patients with DESD, there is a significant improvement in PVRU and Qmax after the injection of BTX-A. Hence, BTX-A injection is an effective method of treatment for DESD. However, further studies and follow-up are required to further evaluate patient satisfaction, quality of life and need for repeated injections.